An Unusual Foreign Body–Caused Chondral Lesion of the Talar Dome: A Case Report. Issue 2 (April 2021) - Hummel, Amelia; Cody, Elizabeth
Abstract : Case: A patient presented with chronic ankle pain and instability. Imaging revealed a talar osteochondral lesion as well as intra-articular loose bodies. Intraoperatively, an unusual, well-demarcated chondral defect was found. A glass fragment was also identified in the joint. The patient subsequently recalled a minor ankle laceration from a shattered glass bottle, suggesting unrecognized foreign body retention as the cause of the cartilage damage. Conclusion: This is the first reported example of glass migrating into the ankle joint, leading to significant cartilage damage. This case highlights the elusive nature of foreign bodies and the difficulty of diagnosis with standard imaging.